Le « pipi au lit » : quelques ressorts pour assurer un contexte favorable à la construction d’une parole collective des enfants en protection de l’enfance - Gilles Séraphin (Sociétés et Jeunesses en Difficulté)
This article is based on the analysis of a scene that took place during a meeting of a group of children involved in the implementation of a citizen’s assembly in child protection, during which a proposal for change emanated when a regularly occurring event for children placed in child protection was emotionally debated: “bedwetting”. Confronting the lessons learned from this event with the international literature on the subject, we deduce that the process of collective child participation rests on four “springs” that condition it: the apprehension of collective participation as a dynamic theatrical stage, a source of struggle for recognition; adaptation to children’s “acted” time and space; acceptance of the expression of shared emotions, which become supports and a gateway to a relationship of trust; and ongoing analysis of the place of adults, who must constantly adapt.